Effects of population, urbanization, household size, and income on electric appliance adoption in the Chinese residential sector towards 2050. (15th February 2019) - Li, Mingquan; Shan, Rui; Hernandez, Mauricio; Mallampalli, Varun; Patiño-Echeverri, Dalia
Highlights: Provide estimates of future adoption of six household electric appliances in China. Urban households in Eastern China will own most of the electric appliances. Ownership of personal computers and air conditioners will grow the most (over 100%). Higher income is the primary reason behind growth in ownership of appliances. Differences in appliance saturation among regions will almost disappear by 2050. Abstract: We present an analytical framework to project adoption of household electric appliances under a number of scenarios with different levels of population, urbanization, household size, and per-capita income. This framework enables us to estimate the saturation (i.e., number of a particular electric appliance per household) and the extent of adoption (total number of a particular electric appliance owned in each province), and to assess the impact of each driver. We focus on six types of appliances: personal computer, air conditioner, microwave oven, refrigerator, washing machine and television, and project their adoption during the 2015–2050 period. The projections are conducted for forty-five scenarios that combine five levels of population growth, three levels of per-capita gross domestic product (GDP) and income growth, and three levels of change in household size. We find that, among the six appliances investigated, ownership of personal computers and air conditioning equipment will grow the most, and that the current differences in appliance saturation among provinces and between urban and rural regions will almost disappear by 2050. However, most of the appliances will be owned in urban centers in Eastern China, where the majority of the population will be concentrated. Income growth, combined with urbanization and a reduction in household sizes, increases the total number of appliances, while a reduction in population decreases the total number of appliances. The results can be used as key inputs for long-term electricity system planning and to explore the potential effects of policies to support End-Use Energy Efficiency and Demand Side Response.